How people make decisions during earthquakes and post-earthquake evacuation: Using Verbal Protocol Analysis in Immersive Virtual Reality. (September 2020) - Feng, Zhenan; González, Vicente A.; Trotter, Margaret; Spearpoint, Michael; Thomas, Jared; Ellis, Debra; Lovreglio, Ruggiero
Highlights: A total of 83 participants were included to the present study. A virtual earthquake drill was conducted using Immersive Virtual Reality. Verbal Protocol Analysis was undertaken to investigate decision-making processes. Results were compared to the results obtained through the analysis of real-life CCTV videotapes. Abstract: Human behavior during earthquakes and post-earthquake evacuation is crucial to earthquake safety. Understanding decision-making processes may explain why people respond in different ways to earthquakes. This information can assist with the development of earthquake evacuation guidelines and practices. Verbal Protocol Analysis (VPA) can be used to investigate decision-making processes. VPA encourages participants to think aloud while they are executing tasks. However, it is difficult to obtain such data during actual earthquakes or traditional evacuation drills. Immersive Virtual Reality (IVR) is an innovative tool that can be applied to investigate human behavior under extreme conditions such as earthquakes. In this study, we used a head-mounted display (HMD)-based IVR for investigating decision-making processes during an earthquake emergency based in Auckland City Hospital. A total of 83 hospital staff and visitors completed the experiment. VPA was carried out along with the IVR. The responses of VPA were analyzed to identify decision-making themes. Results show that participants tended to be influenced by other people, especially those in authority positions, and wanted to accompany other people while evacuating. Participants were also found to have wait-or-flight responses in post-earthquake evacuation. Implications for current earthquake evacuation guidelines and practice are provided based on the results.